MEMBEDAH KASUS KORUPSI GAYUS TAMBUNAN DENGAN PISAU ANOMI - Jetty Martje Patty (SASI, 2015)
Anomie theory put imbalance values and norms in society as the cause of the deviation, where people are grouped in the social structure (forms Class) from the top of society to the public is low, which led to differences of this class opportunity to achieve goals. Gayus Tambunan coming from low class society, have the opportunity to become rich is smaller compared to those with higher grade. This situation makes resulted segregration makes people who do not have the means to do it then do another way to achieve the goal to become rich, for example, or goal he wants